2014
DOI: 10.1111/idh.12079
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial action of Chlorhexidine/thymol containing varnishes in vitro and in vivo

Abstract: Both varnishes may influence the plaque formation and reduce mutans streptococci in supragingival plaque.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 18 publications
(15 reference statements)
1
8
0
2
Order By: Relevance
“…At a closer look to the statistically significant differences between the test and the control groups, one can remark that the differences in the detectability/non‐detectability of some of the tested periopathogens affected only one and two patients in each group, respectively, and thus, it should not be overestimated. In general, the results are similar to findings comparing two CHX varnishes .…”
Section: Discussionsupporting
confidence: 85%
“…At a closer look to the statistically significant differences between the test and the control groups, one can remark that the differences in the detectability/non‐detectability of some of the tested periopathogens affected only one and two patients in each group, respectively, and thus, it should not be overestimated. In general, the results are similar to findings comparing two CHX varnishes .…”
Section: Discussionsupporting
confidence: 85%
“…Although QAMS exhibits broad-spectrum antimicrobial activities against single-species bacterial and fungal biofilms in vitro , the in vivo sensitivity of biofilms to antimicrobial agents against device-related infections may not be as effective as that in vitro 44 . Moreover, some microbial strains may be more sensitive to antimicrobial agents than others 45 . This species diversity exists in vivo but not in multi-species biofilms cultured in vitro .…”
Section: Discussionmentioning
confidence: 99%
“…The evidence from this review was mixed and therefore inconclusive for CHX-V reducing caries risk. More recently, Jentsch et al found CHX-V significantly reduced MS counts in supragingival plaque (P < 0.05) (15).…”
Section: Introductionmentioning
confidence: 93%
“…More recently, Jentsch et al . found CHX‐V significantly reduced MS counts in supragingival plaque ( P < 0.05) .…”
Section: Introductionmentioning
confidence: 99%